Analysis and design aspects of delayed resonator absorber with position, velocity or acceleration feedback - Vyhlídal, Tomáš; Pilbauer, Dan; Alikoç, Baran; Michiels, Wim (Journal of sound and vibration, 2019)
A thorough analysis of six delayed resonator configurations is performed. Considering either lumped or distributed delays, feedback is taken from acceleration, velocity or position measurements. Next to presenting stability maps derived by the Cluster Treatment of Characteristic Roots, the robustness in the vibration suppression is analyzed. It is shown that the deterioration of vibration suppression caused by mismatch between the design and true excitation frequencies can be decreased by a proper selection of the delayed resonator configuration and the frequency operable range. Besides, the force and energy demands from the resonator feedback are studied with respect to the absorber physical parameters. All the results are derived for a dimensionless model form and as such they are universally valid. Thus, with respect to the important design specifications, the analysis is complete and can be used as guidelines for parametrization of the given delayed resonator set, with respect to the operable conditions.